How to report light exposure in human chronobiology and sleep research experiments - Spitschan, M; Stefani, O; Blattner, P; Gronfier, C; Lockley, S; Lucas, R (MDPI, 2019)
Exposure to light has short- and long-term impacts on non-visual responses in humans. While many aspects related to non-visual light sensitivity have been characterised (such as the action spectrum for melatonin suppression), much remains to be elucidated. Here, we provide a set of minimum reporting guidelines for reporting the stimulus conditions involving light as an intervention in chronobiology, sleep research and environmental psychology experiments. Corresponding to the current state-of-the-art knowledge (June 2019), these are (i) measure and report the spectral power distribution of the acute stimulus from the observer’s point of view; (ii) measure and report the spectral power distribution of the background light environment from the observer’s point of view; (iii), make spectra available in tabulated form, (iv) report α-opic (ir)radiances and illuminance; (v) describe the timing properties of stimulus (duration and pattern); (vi) describe the spatial properties of stimulus (spatial arrangement and extent), and (vii) report measurement conditions and equipment. We supplement the minimum reporting guidelines with optional reporting suggestions and discuss limitations of the reporting scheme.